Reformasi Sistem Hukum Pidana di Indonesia Melalui Restorative Justice Untuk Pemulihan Korban dan Pelaku - Tiawarman K., Andriansyah; Redi, Ahmad (JURNAL RETENTUM, 2023)
The application of restorative justice in the Indonesian criminal justice system, highlighting the importance of this approach in creating more humane and effective justice. Restorative justice is considered as an alternative to crime resolution that can support recovery for victims and rehabilitation of perpetrators, as well as reduce the burden on the criminal justice system. This research uses a normative juridical approach, which focuses on analyzing laws and regulations, legal theories, and expert opinions related to the application of restorative justice. The main findings of this research show that although restorative justice has great potential in resolving criminal cases, its implementation in the field still faces a number of obstacles, such as lack of facilities and infrastructure, limited number of personnel, and the competence of law enforcement officials that still need to be improved. Therefore, reform and strengthening of laws and regulations are needed to ensure a more optimal implementation of restorative justice.